Access point selection algorithm for multi-rate WLANs to optimise throughput and guarantee fairness. (6th September 2011) - Zhao, Yanxiao; Song, Min
A novel Access Point (AP) selection algorithm to maximise the system throughput while considering user fairness is proposed for multi-rate WLANs. When a new-coming user enters an overlapping area of multiple APs, it chooses the one to achieve the highest system throughput. For existing users that locate in the overlapping area, they may also need to change their AP associations due to the dynamic nature of traffic load. To enable the fairness among users, each user is guaranteed a minimum transmission opportunity. In-depth theoretical analysis and extensive simulations are performed to verify the throughput optimisation and user fairness.